The Logistics Performance Index in Oman: A Comprehensive Review Through Multi-Criteria Decision-Making - AL-QASIMI, MANSOOR; KHUDARI, MOHAMED; AL BALUSHI, ZAINAB; ABDuLLAH, AZLINA BTE. (Journal of Ecohumanism, 2024)
The current economy heavily relies on global commerce, where logistics are vital in facilitating the smooth transportation of commodities across international boundaries. The Logistics Performance Index (LPI), created by the World Bank, is a crucial instrument for assessing the logistics systems of nations. It is based on six essential criteria: customs procedures, infrastructure quality, international shipments, logistics competence, tracking and tracing capabilities, and delivery timelines. With its advantageous position on the Arabian Peninsula, Oman could emerge as a prominent centre for logistics. The Omani government’s objective is to convert the nation into a dominant force in logistics, as outlined in its Vision 2040 plan. The logistics industry in Oman plays a crucial role in promoting economic diversification, facilitating integration with global markets, and fostering overall economic development. This research uses the Logistics Performance Index (LPI) and Multi-Criteria Decision-Making (MCDM) approaches to evaluate Oman’s logistics performance. The study also identifies the main areas that need improvement and compares Oman’s performance with that of other countries in the region and globally. The study aims to provide policy suggestions to improve Oman’s logistics industry, supporting its objective of becoming a prominent logistics hub. In addition, the research used an improved gravity model to examine non-oil exports and re-exports, considering variables such as GDP, population growth, distance, and Free Trade Agreements (FTAs). The results demonstrate substantial linkages and provide valuable insights into possible trade possibilities and forthcoming advancements. This study provides policymakers and stakeholders with a helpful tool to facilitate strategic enhancements in Oman’s logistics sector and bolster the nation’s economic strategy.